O niepewności prawdy - Niećko, Bożena (Investigationes Linguisticae, 2010)
The present text focuses on truth and its multidimensionality. Truth is presented in the epistemological, psychological and moral sense. The author introduces the notion of negotiating truth and negotiable truth. Negotiating truth is understood as the truth about/in negotiations, where a typical situation is the lack of sincerity in negotiating games, in various negotiating techniques. The negotiable truth is seen as the truth accepted by the participants of a negotiating process who agree (negotiate) what they will collaboratively regard as truth. Further, the problems of certainty and truth are analysed and exemplified by the use of expressions: tak naprawdę (Eng. really, truelly, at heart) and na pewno (Eng. for certain, for sure, certainly). The analysis of truth from the perspective of subjectivism and relativism is aimed to demonstrate the relative and changeable character of truth(s).